A Comprehensive Study of the Dynamic Interaction Between Normal Labor Pain and Maternal Anxiety Levels: A Multivariable Approach to Analyzing Psychophysiological Influences and Subjective Perceptions - Wijayanegara, Hidayat; H. R., Teni Nurlatifah; Rowawi, Roni; Herawati, Yanti (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
Normal labor is a complex physical and emotional experience for a mother, with pain being a major element in this process. The interaction between labor pain and maternal anxiety levels is an aspect that requires in-depth understanding, given its influence on the psychophysical well-being of both mother and baby. Although the scientific literature has highlighted the importance of pain and anxiety management during labor, comprehensive studies that consider the psychophysiological and subjective perceptual influences on this dynamic interaction are limited. Therefore, this study aimed to explore the relationship between pain in normal labor and maternal anxiety levels through a multivariable approach. This research method uses a quantitative approach with an analytic observational research type. The research design was conducted prospectively. This research method involves maternal respondents who experience normal labor, with data collection through measuring anxiety levels using standardized questionnaires and psychophysiological analysis using objectively measured parameters. In addition, a multivariable approach was used to analyze the complexity of the interaction between the variables involved. The sample size was 100 laboring mothers, randomly selected from the population of mothers who met the inclusion criteria. The population was mothers giving birth at TPMB Midwife Delima in Bandung City. Using cluster sampling, only 40 pomegranate midwives (10 sub-districts) were taken from a total of 127 pomegranate midwives from 30 sub-districts. The results showed that the average level of pain during labor reached 6.8 with an average duration of 8 hours. The average maternal anxiety level reached 55 on a scale of 0-100. A significant correlation was found between pain and anxiety (r = 0.68, p < 0.05), while psychophysiological influences such as frequency of uterine contractions and blood pressure also played a role in the experience of pain. Social support was also shown to influence anxiety levels (p = 0.005). These findings illustrate the complexity of interactions between psychophysiological and social aspects in the context of normal labor, providing a basis for the development of more targeted intervention strategies in the management of maternal pain and anxiety. The conclusion of this study shows that there is a significant relationship between pain in normal labor and maternal anxiety levels. Psychophysiological influences, such as frequency of uterine contractions and blood pressure, as well as social support, play an important role in determining the mother's experience during labor. Therefore, increased attention to pain management and provision of adequate social support may be key to reducing maternal anxiety levels. A suggestion for health practitioners is to strengthen efforts to integrate holistic pain management strategies and enhance aspects of social support during normal labor, in the hope of improving the mother's overall emotional and physical well-being.